The Effect of Tax Knowledge and Tax Socialization on Motivation to Pay Taxes in STIE Eka Prasetya Students - Tanelwy, Aurellia; Kosasih, Jocelin; Calosa, Charen; Caroline; Jesslyn; Stefanie; Tina Muhardika Handayani; Bambang Sutejo; Sudirman (Outline Journal of Management and Accounting, 2024)
This study aims to determine the effect of partially or simultaneously Tax Knowledge and tax Socialixation on Motivation to Pay Taxes. The population in this study are STIE Eka Prasetya Students. The sampling technique in this study used saturated samples, which amounted to 35 students of 20.1 class. The research method used is the technique of collecting data through questionnaires. The analytical method used to solve problems and prove hypotheses is descriptive analysis, regression analysis. Partially Tax Knowledge has a positive and significant effect on Motivation to Pay Taxes and Tax Socialization has a positive and significant effect on Motivation to Pay Taxes. Simultaneously Tax Knowledge and Tax Socialization have a positive and significant effect on Motivation to Pay Taxes. The coefficient of determination test results (R2) shows that 56,1% of the Motivation to Pay Taxes variable is influenced by the Tax Knowledge and Tax Socializationvariable, while the remaining 43,9% is influenced by other variables outside of this study.